Macroeconomic volatility, macroeconomic performance and institutional quality in emerging and developing countries - Shah, Said Zamin (2017)
This study investigates the three inter-related but different issues accounting the interactions and volatility transmissions between macroeconomic volatility and macroeconomic performance, and the role of institutional quality on macroeconomic volatility in emerging and developing countries. Specifically, the first objective deals with the dynamic causal links and volatility spillovers between macroeconomic uncertainty and macroeconomic performance, while the second and third theme of this study examine the impact of institutional quality including political and economic institutions on macroeconomic volatility such as output growth volatility and inflation volatility in emerging and developing countries. Specifically, the policy success to embrace prime targets for inflation and output growth is difficult to imagine without considering their variabilities around their target levels. However, there is no consensus among the existing literature regarding the nexus and volatility spillovers between macroeconomic uncertainty and performance. Thus, keeping a unique and more fascinating region whose recent risks to robust economic growth always include the threat of inflation and particularly, inflation uncertainty and volatile growth in South Asia remain tilted on the upside as compared to other regions. Hence, the first objective seeks to address this situation by examining the dynamic causal links and volatility spillovers of inflation, output growth and their uncertainties in four South Asian countries (Pakistan, India, Bangladesh and Sri Lanka). Through the lens of multivariate GARCH family models, we find that only four of the testable hypotheses have common supports. First, there is an overwhelming support for Friedman-Ball hypothesis that inflationary shocks increase inflation uncertainty in all countries. Second, output growth is reducing real volatility in all countries except Sri Lanka. Third, inflation uncertainty improves output growth in all but one country—India. Fourth, the Black’s argument, i.e., output volatility leads to improve output growth is found to hold in the majority of these countries. For the remaining hypotheses, we observe that the relationships tend to be country-specific, such as the Cukierman-Meltzer’s hypothesis is unique in Bangladesh and Sri Lanka while the Holland’s arguments hold for India and Pakistan only. Finally, the statistical significance of the spillovers effects in some of the countries implies that innovations to inflation (real activity) significantly influence real (nominal) uncertainty. The estimated results are almost robust with the alternative estimation strategies. Thus policy makers in these countries should pay more attentions to expectations formations and should adopt dynamic stabilization and inflation targeting strategies, coupled with sustainable growth. Next, while considering macroeconomic volatility as heavily rooted in developing world with a higher welfare cost since the last few decades, the second objective of this study shed light over the relatively new and on-going debate on the effects of institutional infrastructure on output growth volatility in a diverse sample of emerging and developing countries. The precise role of both political and economic institutional measures is investigated here to check whether the various dimensions of these institutions have statistically significant impact on output growth volatility. In doing so, first we open the black-box of political institutions by emphasizing the key aspects of political system such as type and strength of political regime, political stability, institutions and quality of governance, and the competitiveness and accountability of political regime. Second, this study also explores whether underlying market supporting institutions and their various components have any mitigating effect on output growth volatility. While investigating the aggregated and disaggregated effects of both versions of institutions on output volatility through Generalized Method of Moments (GMM) estimators, we find that the concerned institutional details are of crucial importance for stabilizing effect. In general, output growth is less volatile in countries that adopt quality and stable democratic system, have stronger quality of governance and that have higher political constraints. We also find strong evidence that economic institutional development and its various components lead to less macroeconomic volatility. In addition, this study also contributes by identifying the indirect or indexing role of institutional arrangements through their interaction effects with volatility of fundamentals in influencing output growth stability. The estimated results appear to hold intact against a variety of standard robustness checks. This study contributes to the institutional design debate that emphasis merely on macroeconomic policies might not be sufficient to foster a more stable growth path in emerging and developing countries. Finally, while considering the doctrine of Washington consensus and the recent conjecture that weak institutions are the root cause of volatile macroeconomic outcomes and distortionary policies, the third part of this study examines whether data supports such contentions. Specifically, it focuses why inflation tends to be more volatile in the small, open and emerging market economies. Using a dynamic panel approach, the empirical analysis suggests that politico-economic institutional arrangements including highly democratic regimes, political stability, institutional quality, constraints on political powers and market supporting arrangements play a key role for explaining the cross-country variations in inflation volatility. Other variables, related to economic growth, financial development, exposure to external shocks and volatility of fundamentals are also significant determinants of inflation volatility. The study also confirms that the various aspects of both political and economic institutions help to reduce the volatility effects of several endogenous and exogenous shocks. Overall, the main conclusions are found robust to a number of sensitivity checks. The empirical findings imply that developing and emerging countries can have higher welfare gains of macroeconomic stability from efforts to improve qualities of political and economic institutional cluster.